Single-component low-density self-leveling flame-retardant silicone sealant as well as preparation method and application thereof
By developing a single -frame low -density self -leveling flame -retardant silicone sealing, the problem of high existing sealing gel density, poor tactitivity, poor flame retardant performance, and poor humidity and heat resistance. Lightweight, high efficiency and safety needs.
Patent Information
- Application Number
- CN202411269513.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicone sealant used for battery pack sealing has high density, poor thixotropy, poor flame retardant performance and poor humidity and heat resistance, which cannot meet the needs of battery packs for lightweight, high efficiency and safety.
Develop a single-frame low-density self-leveling flame-retardant silicone sealant, and reasonably formulate α, ω-dihydroxycopic polymailing silicone, dioma silicon oil, hollow ceramic beads, nanoccarbonate, flame retardant, flame retardant, flame retardant The agent, polyether modifiers, siliconane, crosslinking agent, coupling agent and catalyst form a sealing glue with high tactile and self -leveling characteristics.
The low density, high-touch and self-flowing effect of sealing gels have been achieved, with V-0-level flame retardant performance and good humidity and heat resistance, reduce the overall weight of the battery pack, improve production efficiency, and enhance the battery pack Safety.
Smart Images

Figure BDA0005038275290000051 
Figure BDA0005038275290000061 
Figure BDA0005038275290000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicone sealants, and in particular relates to a single-component low-density self-leveling flame-retardant silicone sealant and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy vehicles, automotive lithium batteries, as the core component of new energy vehicles, have also made great progress in recent years towards high energy density and high safety. Various packaging technologies for battery packs are also constantly iterating and updating, but the adhesives currently used for sealing in battery packs have the following technical problems: high density, which increases the overall weight of the battery pack; poor thixotropy, requiring additional smoothing steps or too much flow, requiring cleaning after application, which is not conducive to improving production efficiency; poor flame retardant performance, which cannot meet the safety requirements of battery packs; poor moisture and heat resistance, and the sealant fails after multiple charge and discharge of the battery.
[0003] Chinese patent CN03117403.5 discloses a neutral silicone fireproof sealant, whose fireproof and flame-retardant performance reaches FV-0 level of GB / T2408-1996, and has good adaptability to substrates such as concrete, glass, stone and metal; however, its sag is zero according to GB / T13477 test, indicating that its fluidity is poor and it cannot achieve self-leveling effect. Chinese patent CN114106767A discloses a low specific gravity fireproof silicone sealant, especially the results show that the minimum specific gravity is 1.23g / cm 3 , is still very high, and it is not clearly stated whether it can achieve the purpose of self-leveling.
[0004] Therefore, there is an urgent need to provide a low-density self-leveling flame-retardant silicone sealant that can reduce weight and improve efficiency when used for sealing in battery packs, and has excellent flame retardancy and moisture and heat resistance. Summary of the invention
[0005] In view of this, the present invention provides a one-component low-density self-leveling flame-retardant silicone sealant and a preparation method and application thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A one-component low-density self-leveling flame-retardant silicone sealant, the sealant comprising the following array parts by weight: 45-60 parts of α,ω-dihydroxy polydimethylsiloxane, 35-50 parts of dimethyl silicone oil, 20-30 parts of hollow ceramic microspheres, 15-25 parts of nano calcium carbonate; 15-25 parts of flame retardant, 5-8 parts of polyether modified siloxane, 4-6 parts of cross-linking agent, 4-6 parts of coupling agent, and 0.4-1.0 parts of catalyst;
[0008] Wherein, the polyether-modified siloxane is prepared by reacting allyl polyether, 107 glue and platinum catalyst;
[0009] The viscosity of the allyl polyether is 800-1000 mPa·S, the viscosity of 107 glue is 1000-1500 mPa·S, and the platinum catalyst is a Custer platinum catalyst.
[0010] Furthermore, the preparation method of the polyether-modified siloxane is as follows: the allyl polyether, 107 glue and platinum catalyst are mixed in a mass ratio of (100-120): (30-50): (0.2-0.4), the temperature is raised to 120°C, the mixture is stirred and reacted for 4 hours, the temperature is then lowered to 40°C, and the mixture is stirred and reacted for 30 hours to obtain the polyether-modified siloxane.
[0011] Furthermore, the allyl polyether, 107 glue and platinum catalyst are mixed in a mass ratio of 100:50:0.2.
[0012] Furthermore, the viscosity of the α,ω-dihydroxypolydimethylsiloxane is 50,000 to 100,000 mPa·S; and the viscosity of the dimethyl silicone oil is 100 to 500 mPa·S.
[0013] Furthermore, the hollow ceramic micro-D50 particle size is 90-100 μm and the density is 0.60-0.80 g / cm 3 The specific surface area of the nano calcium carbonate is 20 to 22 m 2 / g; the flame retardant is at least one of aluminum hydroxide, aluminum oxide, and magnesium oxide, and the flame retardant D50 particle size is 10 to 15 μm.
[0014] Furthermore, the crosslinking agent is one or two of methyltrimethoxysilane, dimethyldimethoxysilane and vinyltrimethoxysilane.
[0015] Furthermore, the coupling agent is at least one of γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
[0016] Furthermore, the catalyst is a titanate catalyst.
[0017] The preparation method of the above-mentioned sealant comprises the following steps:
[0018] Mix α,ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, hollow ceramic microspheres, nano calcium carbonate and flame retardant according to weight proportions, raise the temperature to 110-130°C, evacuate to above -0.09MPa, and keep warm for dehydration for 2h;
[0019] After dehydration, cool to 40-50°C, add polyether-modified siloxane, and stir for 15-20 minutes. Continue to cool to 25-35°C, add crosslinking agent, coupling agent and catalyst, keep the vacuum degree above -0.09MPa, and continue stirring for 30 minutes to obtain the sealant.
[0020] Application of the above sealant in sealing of battery packs.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The single-component low-density self-leveling flame-retardant silicone sealant provided by the present invention is mainly used for caulking and sealing between battery blocks. The sealant has high thixotropy and self-leveling properties. The thixotropy index of the colloid after application is between 21.6 and 22.4, which can achieve flow and fill the glue seam without overflowing, thus reducing the production steps. At the same time, it can achieve V-0 flame retardant performance, improve the overall safety of the battery, and the density of the colloid is less than 1g / cm 3 , and will not have a significant impact on the overall quality of the battery pack. The Shore hardness of this product can be achieved below 25A, which can withstand the extrusion of the colloid due to the deformation of the battery during charging and discharging; the thixotropic agent used is polyether-modified siloxane, which has good compatibility with the silicone system, and an appropriate amount of nano-calcium carbonate is used to improve the aging resistance. After high temperature and high humidity aging, the sealant will not appear powdering or viscosity increase. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.
[0024] The one-component low-density self-leveling flame-retardant silicone sealant provided by the present invention is prepared as follows:
[0025] S1, by mass: 45-60 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 50000-100000 mPa·S, 35-50 parts of dimethyl silicone oil with a viscosity of 100-500 mPa·S, D50 particle size of 90-100 μm, density of 0.60-0.80 g / cm 3 20-30 parts of hollow ceramic microspheres with a specific surface area of 20-22m 2 / g of nano calcium carbonate 15-25 parts, D50 particle size of 10-15μm flame retardant, mix evenly, stir and heat to 110-130℃, evacuate, keep the vacuum degree above -0.09MPa, and keep warm for 2h.
[0026] S2. After dehydration, cool to 40-50° C., add 5-8 parts of polyether-modified siloxane by mass, and stir at this temperature for 15-20 minutes.
[0027] S3, continue stirring and cool to 25-35°C, add 4-6 parts of cross-linking agent, 4-6 parts of coupling agent and 0.4-1.0 parts of catalyst by mass, maintain the vacuum degree above -0.09MPa, continue stirring for 30 minutes, after the reaction is completed, pour the glue into the hose and seal it for storage, so as to obtain the sealant.
[0028] Among them, the preparation method of the polyether-modified siloxane is as follows: allyl polyether with a viscosity of 800-1000mPa·S, 107 glue with a viscosity of 1000-1500mPa·S, and a platinum catalyst are mixed in a mass ratio of (100-120): (30-50): (0.2-0.4), heated to 120°C, stirred and reacted for 4 hours, then cooled to 40°C, stirred and reacted for 30 hours, and the polyether-modified siloxane is obtained.
[0029] Example 1
[0030] This embodiment provides a one-component low-density self-leveling flame-retardant silicone sealant and a preparation method thereof. The specific material composition is shown in the following table:
[0031] Specific material name or model Dosage (portion) α,ω-dihydroxypolydimethylsiloxane (80000mPa·S) 55 Dimethyl silicone oil (500mPa·S) 40 <![CDATA[Hollow ceramic microspheres (100μm, 0.6g / cm 3 )]]> 30 <![CDATA[Calcium carbonate nanometer 22m 2 / g]]> 15 Aluminum hydroxide 10μm 20 Polyether modified siloxane 6 Methyltrimethoxysilane 5 γ-Aminopropyltrimethoxysilane 4 N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane 2 Titanate Catalyst 0.5
[0032] Among them, the preparation method of polyether modified siloxane is as follows: take allyl polyether with a viscosity of 800mPa·S, 107 glue with a viscosity of 1000mPa·S and Custer platinum catalyst in a mass ratio of 100:50:0.2, add them into a flask and mix them evenly, first heat the oil bath to 120°C, keep stirring for 4 hours, then cool to 40°C, stir at a low speed for 30 minutes, and obtain polyether modified siloxane.
[0033] The preparation method of the single-component sealant is as follows: add 107 glue (α, ω-dihydroxypolydimethylsiloxane), dimethyl silicone oil, hollow ceramic microspheres, nano-calcium carbonate, and flame retardant into the reaction kettle according to the weight parts in the above table, stir and heat to 120°C, evacuate, maintain the vacuum degree above -0.09MPa, and keep warm for dehydration for 2 hours; cool to 45°C after dehydration, add polyether modified siloxane, and continue stirring for 20 minutes; after stirring, cool to 30°C, add a cross-linking agent, a coupling agent and a catalyst, maintain the vacuum degree above -0.09MPa, continue stirring for 30 minutes, discharge the glue into a hose and seal it for storage to obtain the sealant.
[0034] Example 2
[0035] This embodiment provides a one-component low-density self-leveling flame-retardant silicone sealant and a preparation method thereof. The specific material composition is shown in the following table:
[0036]
[0037]
[0038] Among them, the preparation method of polyether-modified siloxane is as follows: The preparation method of polyether-modified siloxane is as follows: Take allyl polyether with a viscosity of 800mPa·S, 107 glue with a viscosity of 1000mPa·S and Custer platinum catalyst in a mass ratio of 110:40:0.3, add them into a flask and mix them evenly, first heat the oil bath to 120°C, keep stirring for 4 hours, then cool to 40°C, stir at a low speed for 30 minutes, and obtain polyether-modified siloxane.
[0039] The preparation method of the single-component sealant is the same as that in Example 1.
[0040] Example 3
[0041] This embodiment provides a one-component low-density self-leveling flame-retardant silicone sealant and a preparation method thereof. The specific material composition is shown in the following table:
[0042] Specific material name or model Dosage (portion) α,ω-dihydroxypolydimethylsiloxane (50000mPa·S) 50 Dimethyl silicone oil (100mPa·S) 40 <![CDATA[Hollow ceramic microspheres (90μm, 0.8g / cm 3 )]]> 30 <![CDATA[Calcium carbonate nanoparticles 20m 2 / g]]> 15 Aluminum hydroxide 10μm 20 Polyether modified siloxane 6 Methyltrimethoxysilane 5 γ-Aminopropyltrimethoxysilane 4 γ-Methacryloyloxypropyltrimethoxysilane 2 Titanate Catalyst 0.5
[0043] Among them, the preparation method of polyether modified siloxane is as follows: take allyl polyether with a viscosity of 1000mPa·S, 107 glue with a viscosity of 1500mPa·S and Custer platinum catalyst in a mass ratio of 100:50:0.2, add them into a flask and mix them evenly, first heat the oil bath to 120°C, keep stirring for 4 hours, then cool to 40°C, stir at a low speed for 30 minutes, and obtain polyether modified siloxane.
[0044] The preparation method of the single-component sealant is the same as that in Example 1.
[0045] Comparative Example 1
[0046] This comparative example provides a one-component low-density self-leveling flame-retardant silicone sealant, whose constituent materials and preparation method are basically the same as those of Example 1, except that the hollow ceramic microspheres are replaced by hollow glass microspheres of equal mass, and the rest remain unchanged.
[0047] Comparative Example 2
[0048] This comparative example provides a one-component low-density self-leveling flame-retardant silicone sealant, whose constituent materials and preparation method are basically the same as those of Example 1, except that the nano calcium carbonate in the material is removed, and the rest remains unchanged.
[0049] Comparative Example 3
[0050] This comparative example provides a one-component low-density self-leveling flame-retardant silicone sealant, whose constituent materials and preparation method are basically the same as those of Example 1, except that the polyether-modified siloxane is replaced by an equal mass of fumed silica, and the rest remain unchanged.
[0051] Comparative Example 4
[0052] This comparative example provides a one-component low-density self-leveling flame-retardant silicone sealant, whose constituent materials and preparation method are basically the same as those in Example 1, except that the polyether-modified siloxane is replaced by an equal mass of polyether-modified silicone oil (purchased from Guangzhou Tianci High-tech Materials Co., Ltd.), and the rest remain unchanged.
[0053] Comparative Example 5
[0054] This comparative example provides a one-component low-density self-leveling flame-retardant silicone sealant, whose constituent materials and preparation method are basically the same as those in Example 1, except that the amount of α, ω-dihydroxypolydimethylsiloxane is changed from 55 parts to 40 parts, the amount of hollow ceramic microspheres is changed from 30 parts to 15 parts, and the rest remain unchanged.
[0055] Comparative Example 6
[0056] This comparative example provides a one-component low-density self-leveling flame-retardant silicone sealant, whose constituent materials and preparation method are basically the same as those in Example 1, except that the viscosity of α, ω-dihydroxypolydimethylsiloxane is changed from 8000mPa·S to 20000mPa·S, and the viscosity of dimethyl silicone oil is changed from 500mPa·S to 100mPa·S, and the rest remain unchanged.
[0057] Furthermore, in order to understand the performance of the sealants prepared in the above embodiments and comparative examples, the following tests were conducted, wherein each test was conducted with reference to national standards GB / T 13477 and GB / T2408. The specific test results are shown in Table 1 below.
[0058] Table 1 Performance of each sealant prepared
[0059]
[0060] As shown in Table 1, the sealant prepared by the present invention has a benchmark time of 25 to 37 minutes, a Shore A hardness of 21 to 24 HA, a flame retardant grade of V0, and a density of 0.94 to 0.99 g / cm 3 The thixotropic index is between 21.6 and 22.4. After aging, the double 85 shows the characteristics of no powdering and viscosity increase; the comprehensive indicators are excellent, achieving the technical effect of low-density self-leveling and flame retardant. When used for sealing in battery packs, it can achieve the purpose of reducing weight, improving efficiency, and excellent flame retardancy and moisture and heat resistance.
[0061] Compared with the sealant prepared in the present application, hollow glass microspheres are used in the sealant prepared in Comparative Example 1, which has a lower density and a lower hardness than hollow ceramic microspheres, but its high temperature resistance is not as good as that of hollow ceramic microspheres, resulting in a lower density and a smaller thixotropic index for the prepared sealant, which makes it easier to achieve a self-leveling effect, but its hardness and flame retardant effect are poor. No nano-calcium carbonate was added in Comparative Example 2, resulting in a low thixotropic index, and the sealant will flow freely during transition, which is not conducive to operation, and the resistance to wet heat aging is also reduced. In Comparative Example 3, gas silicon is used as a thixotropic agent, resulting in a thixotropic index that is too high, and the sealant cannot achieve self-leveling. A cleaning process will be added later, which reduces efficiency. Comparative Example 4 uses polyether modified silicone oil as a thixotropic agent. Due to the large viscosity of the modified silicone oil, it is used in combination with nano-calcium carbonate, which makes the thixotropy of the sealant too high, and the self-leveling effect cannot be achieved. Comparative Example 5 reduces the amount of α, ω-dihydroxypolydimethylsiloxane and aluminum hydroxide, resulting in a faster surface drying time, improved product hardness and density, and a lower flame retardant grade; Comparative Example 6 uses low-viscosity α, ω-dihydroxypolydimethylsiloxane and dimethyl silicone oil instead, resulting in a slower surface drying time, higher product hardness, worse thixotropic index, and no longer being able to achieve self-leveling.
[0062] The specific raw materials not described in the present invention are all existing materials and can be directly purchased from the market.
[0063] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A one-component low-density self-leveling flame-retardant silicone sealant, characterized in that: The sealant comprises the following parts by weight: 45-60 parts of α,ω-dihydroxy polydimethylsiloxane, 35-50 parts of dimethyl silicone oil, 20-30 parts of hollow ceramic microspheres, 15-25 parts of nano calcium carbonate; 15-25 parts of flame retardant, 5-8 parts of polyether modified siloxane, 4-6 parts of crosslinking agent, 4-6 parts of coupling agent, and 0.4-1.0 parts of catalyst; Wherein, the polyether-modified siloxane is prepared by reacting allyl polyether, 107 glue and platinum catalyst; The viscosity of the allyl polyether is 800-1000 mPa·S, the viscosity of 107 glue is 1000-1500 mPa·S, and the platinum catalyst is a Custer platinum catalyst.
2. The sealant according to claim 1, characterized in that: The preparation method of the polyether-modified siloxane is as follows: the allyl polyether, 107 glue and platinum catalyst are mixed in a mass ratio of (100-120): (30-50): (0.2-0.4), the temperature is raised to 120° C., the mixture is stirred and reacted for 4 hours, the temperature is then lowered to 40° C., and the mixture is stirred and reacted for 30 hours to obtain the polyether-modified siloxane.
3. The sealant according to claim 2, characterized in that: The allyl polyether, 107 glue and platinum catalyst are mixed in a mass ratio of 100:50:0.
2.
4. The sealant according to claim 1, characterized in that: The viscosity of the α,ω-dihydroxy polydimethylsiloxane is 50000-100000 mPa·S; the viscosity of the dimethyl silicone oil is 100-500 mPa·S.
5. The sealant according to claim 1, characterized in that: The hollow ceramic microspheres have a D50 particle size of 90 to 100 μm and a density of 0.60 to 0.80 g / cm 3 The specific surface area of the nano calcium carbonate is 20 to 22 m 2 / g; the flame retardant is at least one of aluminum hydroxide, aluminum oxide, and magnesium oxide, and the flame retardant D50 particle size is 10 to 15 μm.
6. The sealant according to claim 1, characterized in that: The crosslinking agent is one or two of methyltrimethoxysilane, dimethyldimethoxysilane and vinyltrimethoxysilane.
7. The sealant according to claim 1, characterized in that: The coupling agent is at least one of γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
8. The sealant according to claim 1, characterized in that: The catalyst is a titanate catalyst.
9. A method for preparing the sealant according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mix α,ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, hollow ceramic microspheres, nano calcium carbonate and flame retardant according to weight proportions, raise the temperature to 110-130°C, evacuate to above -0.09MPa, and keep warm for dehydration for 2h; After dehydration, cool to 40-50°C, add polyether-modified siloxane, and stir for 15-20 minutes. Continue to cool to 25-35°C, add crosslinking agent, coupling agent and catalyst, keep the vacuum degree above -0.09MPa, and continue stirring for 30 minutes to obtain the sealant.
10. Use of the sealant described in any one of claims 1 to 8 in sealing a battery pack.
Citation Information
Patent Citations
Low-specific-gravity fireproof silicone sealant and preparation method thereof
CN114106767A
Neutral silicone fire-retardent sealing glue and its preparing method
CN1438289A